Langit dan bumi yang Baru: Fondasi Untuk Masa Depan Berkelanjutan - Pris Kristiani Ndraha; Aprianus Lendrik Moimau (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
How Christian teachings teach human responsibility to protect and care for the environment, by citing biblical teachings that support sustainable social justice. This can also include efforts by churches and Christian communities to promote ecological practices and promote some of their missions. In the context of Christian teachings, it is important to explain that the concept of environmental responsibility comes from the belief that God created the universe and empowered humans to protect it (Genesis 2:15). This encourages Christians to take responsibility for their actions towards nature and living creatures. Many Christian denominations emphasize the importance of preserving the environment as part of their moral and ethical obligations. They view environmental destruction as a violation of God's obligation to protect the earth. Awareness of the importance of the environment is a process that must be initiated for the survival of future generations, so that it is not affected by irresponsible human behavior today. The aim of environmental education is to introduce different values and clarify concepts in order to develop the attitudes and skills needed to understand and appreciate the interrelationships of humans, culture and the biophysical environment. The aim of this research is to dig deeper into the development of environmental awareness in Christian education.